MicroRNAs as Important Regulators Mediate the Multiple Differentiation of Mesenchymal Stromal Cells - Yang, Chao; Luo, Maowen; Chen, Yu; You, Min; Chen, Qiang (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs) are endogenous short non-encoding RNAs which play a critical role on output of the proteins, and influence multiple biological characteristics of the cells and physiological processes in the body. Mesenchymal stem cells (MSCs) are adult pluripotent stem cells and characterized by self-renewal and multi-differentiation, and have been widely used for diseases treatment and regenerative medicine. Meanwhile, MSCs play a critical role in maintaining homeostasis in the body, and dysfunction of MSCs differentiation lead to many diseases. The differentiation of MSCs is a complex physiological process and the results of programmed expression of a series of genes. It has been intensively proven that the differentiation process or programmed genes expression is also regulated accurately by miRNAs. The differentiation of MSCs regulating by miRNAs are also a complex, dependent and dynamic process, and fully understanding of the role of miRNAs will provide clues on the appropriate upregulation or downregulation of corresponding miRNAs to mediate the MSCs differentiation efficiency. This article summarizes the roles and concerned signaling pathways of miRNAs in adipogenesis, chondrogenesis and osteogenesis of MSCs, which may provide new hints on MSCs as therapeutic strategies for regenerative medicine and biotherapy for related diseases.